Mettl3-/Mettl14-mediated mRNA N6-methyladenosine modulates murine spermatogenesis - Lin, Zhen; Hsu, Phillip J; Xing, Xudong; Fang, Jianhuo; Lu, Zhike; Zou, Qin; Zhang, Ke-Jia; Zhang, Xiao; Zhou, Yuchuan; Zhang, Teng; Zhang, Youcheng; Song, Wanlu; et al. (Cell research, 2017)
Spermatogenesis is a differentiation process during which diploid spermatogonial stem cells （SSCs） produce hap- loid spermatozoa. This highly specialized process is precisely controlled at the transcriptional, posttranscriptional, and translational levels. Here we report that N6-methyladenosine （m6A）, an epitranscriptomic mark regulating gene expression, plays essential roles during spermatogenesis. We present comprehensive m6A mRNA methylomes of mouse spermatogenic cells from five developmental stages： undifferentiated spermatogonia, type At spermatogonia, preleptotene spermatocytes, pachytene/diplotene spermatocytes, and round spermatids. Germ cell-specific inactiva- tion of the m6A RNA methyltransferase Mettl3 or Mettll4 with Vasa-Cre causes loss of m6A and depletion of SSCs. m6A depletion dysregulates translation of transcripts that are required for SSC proliferation/differentiation. Com- bined deletion of Mettl3 and Mettll4 in advanced germ cells with Stra8-GFPCre disrupts spermiogenesis, whereas mice with single deletion of either Mettl3 or Mettll4 in advanced germ cells show normal spermatogenesis. The sper- matids from d6uble-mutant mice exhibit impaired translation of haploid-specific genes that are esseritial for spermio- genesis. This study highlights crucial roles of mRNA m6A modification in germline development, potentially ensuring coordinated translation at different stages of spermatogenesis.